If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 900x + -1v + 73r + -1px + -2 + -1p = 529 Reorder the terms: -2 + -1p + -1px + 73r + -1v + 900x = 529 Solving -2 + -1p + -1px + 73r + -1v + 900x = 529 Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '2' to each side of the equation. -2 + -1p + -1px + 73r + -1v + 2 + 900x = 529 + 2 Reorder the terms: -2 + 2 + -1p + -1px + 73r + -1v + 900x = 529 + 2 Combine like terms: -2 + 2 = 0 0 + -1p + -1px + 73r + -1v + 900x = 529 + 2 -1p + -1px + 73r + -1v + 900x = 529 + 2 Combine like terms: 529 + 2 = 531 -1p + -1px + 73r + -1v + 900x = 531 Add '-73r' to each side of the equation. -1p + -1px + 73r + -1v + -73r + 900x = 531 + -73r Reorder the terms: -1p + -1px + 73r + -73r + -1v + 900x = 531 + -73r Combine like terms: 73r + -73r = 0 -1p + -1px + 0 + -1v + 900x = 531 + -73r -1p + -1px + -1v + 900x = 531 + -73r Add 'v' to each side of the equation. -1p + -1px + -1v + v + 900x = 531 + -73r + v Combine like terms: -1v + v = 0 -1p + -1px + 0 + 900x = 531 + -73r + v -1p + -1px + 900x = 531 + -73r + v Add '-900x' to each side of the equation. -1p + -1px + 900x + -900x = 531 + -73r + v + -900x Combine like terms: 900x + -900x = 0 -1p + -1px + 0 = 531 + -73r + v + -900x -1p + -1px = 531 + -73r + v + -900x Reorder the terms: -531 + -1p + -1px + 73r + -1v + 900x = 531 + -73r + v + -900x + -531 + 73r + -1v + 900x Reorder the terms: -531 + -1p + -1px + 73r + -1v + 900x = 531 + -531 + -73r + 73r + v + -1v + -900x + 900x Combine like terms: 531 + -531 = 0 -531 + -1p + -1px + 73r + -1v + 900x = 0 + -73r + 73r + v + -1v + -900x + 900x -531 + -1p + -1px + 73r + -1v + 900x = -73r + 73r + v + -1v + -900x + 900x Combine like terms: -73r + 73r = 0 -531 + -1p + -1px + 73r + -1v + 900x = 0 + v + -1v + -900x + 900x -531 + -1p + -1px + 73r + -1v + 900x = v + -1v + -900x + 900x Combine like terms: v + -1v = 0 -531 + -1p + -1px + 73r + -1v + 900x = 0 + -900x + 900x -531 + -1p + -1px + 73r + -1v + 900x = -900x + 900x Combine like terms: -900x + 900x = 0 -531 + -1p + -1px + 73r + -1v + 900x = 0 The solution to this equation could not be determined.
| 0=-16t^2+30t-10 | | 0=-16t^2+30-10 | | 8x^2=-64 | | 4(x-4)=3(1.5+5) | | y-(-1)=(7/8)(x-6) | | 3x-6-x=2 | | 3x+(-2)-8(3x+4)=x-4 | | 3x+(-2)-8(-3x+4)=x-4 | | m+7/12=-5/18 | | 2x-30+x=180 | | y=4x-21 | | 2x+5x-14= | | (x-1)/-4=-6 | | 32-2.6y=.75y+5 | | (-16x^2)+45x+2.5=0 | | 33/4+n=65/8 | | -2(5r+15)=400 | | 4x+2=-6y | | 3(b-9)=-18 | | 2/3*9+12=9-15 | | 2/3*9+12=9-15 | | 1+4x=x+9 | | -11+5r=34 | | 8*3.14=2*3.14x | | 3-10b=2p-9 | | 39.1g= | | 3x+-5=11 | | 14x-5=9x-5 | | -y+24=360 | | 3/4*4/3 | | 0.12*27.95+0.32*12.95=x | | 3x/4=9/16 |